2000
DOI: 10.1136/heart.83.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Antianginal and anti-ischaemic efficacy of tedisamil, a potassium channel blocker

Abstract: Objective-To determine the eYcacy and safety of the potassium channel blocker tedisamil versus placebo in the treatment of patients with stable angina. Design-Prospective, double blind, placebo controlled study. 203 patients first completed a seven day placebo run in. They were then randomised to receive 50 mg, 100 mg or 150 mg tedisamil twice daily, or placebo. Treadmill exercise testing was carried out at baseline and after 14 days of double blind treatment. Main outcome measures-Primary eYcacy parameters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Tedisamil is a bradycardic agent that is in clinical trial for angina (2,3) and heart failure (4). Inhibition of the transient outward potassium current (Ito) of human atrial myocytes (5) probably underlies the bradycardic effect of tedisamil.…”
mentioning
confidence: 99%
“…Tedisamil is a bradycardic agent that is in clinical trial for angina (2,3) and heart failure (4). Inhibition of the transient outward potassium current (Ito) of human atrial myocytes (5) probably underlies the bradycardic effect of tedisamil.…”
mentioning
confidence: 99%
“…Another major advantage is the lack of negative inotropic action. Though tedisamil has been shown to be effective in a dose-dependent fashion in increasing angina threshold and reducing the frequency of angina, it also exhibits reverse dose-dependence, thus limiting its efficacy with exercise and rendering β-blockers superior [50]. In animal studies, tedisamil has been shown to be effective in preventing and reversing ventricular arrhythmia in the ischemic setting [51].…”
Section: Drugs With Class III Actionmentioning
confidence: 97%
“…Tedisamil (KC8857) is a drug tested in ischaemic heart disease due to its bradycardic effect. In coronary artery disease, tedisamil has no effect on inotropism and increases the threshold for angina [65,66]. Its antiarrhythmic properties includes dosedependent lengthening of the ventricular relative and effective refractory periods and prevention of electricallyinduced VF in experimental models of coronary artery occlusion [67].…”
Section: Other Possible Useful Drugsmentioning
confidence: 99%